2016
DOI: 10.3758/s13428-016-0823-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growth mixture models in the presence of time-varying covariates

Abstract: Growth mixture modeling is often used to identify unobserved heterogeneity in populations. Despite the usefulness of growth mixture modeling in practice, little is known about the performance of this data analysis technique in the presence of time-varying covariates. In the present simulation study, we examined the impacts of five design factors: the proportion of the total variance of the outcome explained by the time-varying covariates, the number of time points, the error structure, the sample size, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Significant tests suggest that the target solution can be retained. Simulation studies indicate that the CAIC, BIC, ABIC and BLRT are particularly effective, but that the AIC and LMR should not be used (Diallo et al ., 2016, 2017); these indicators are only reported to ensure a complete disclosure. The entropy will also be reported as an indicator of the quality of the classification of individuals into the extracted profiles, where values closer to 1 indicate better classification.…”
Section: Methodsmentioning
confidence: 99%
“…Significant tests suggest that the target solution can be retained. Simulation studies indicate that the CAIC, BIC, ABIC and BLRT are particularly effective, but that the AIC and LMR should not be used (Diallo et al ., 2016, 2017); these indicators are only reported to ensure a complete disclosure. The entropy will also be reported as an indicator of the quality of the classification of individuals into the extracted profiles, where values closer to 1 indicate better classification.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were conducted using MPlus Version 8.1 (Muthén & Muthén, ). We followed best practices to identify the best fitting model and number of union participator classes (Diallo, Morin, & Lu, , , ). We first examined a two‐class model and increased the number of classes until increases in model fit indicated more classes was no longer parsimonious, which is consistent with other LCA/LPA research (Bennett, Gabriel, Calderwood, Dahling, & Trougakos, ; Gabriel et al., ; Morin et al., ; Woo & Allen, ).…”
Section: Methodsmentioning
confidence: 99%
“…To identify the best fitting model, we examined five fit indices: loglikelihood (LL), Akaike information criterion (AIC), consistent AIC (C‐AIC; the BIC plus the number of free parameters), Bayesian information criterion (BIC), sample‐size‐adjusted BIC (SSA‐BIC), and the Bootstrap likelihood ratio test (BLRT; Diallo et al., , , ; Tofighi & Enders, ). Entropy—a measure of classification accuracy—provides useful information but should not be used for determining model selection (Lubke & Muthén, ) as it penalizes models with a larger number of classes and heavily penalizes LTA results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we followed common practice, relying on the most widely used fit and test statistics: the Akaike's Information Criterion (AIC; Akaike, 1987), Bayesian Information Criterion (BIC, Schwarz, 1978), sample size adjusted BIC (SBIC; Sclove, 1987), Lo-Mendell-Rubin likelihood ratio test (LMR; Lo et al, 2001). Recent simulation studies have, however, indicated that the BIC, SBIC, and LRT are more effective for identifying the correct number of classes (Diallo et al, 2016a(Diallo et al, , 2016b(Diallo et al, , 2017Peugh and Fan, 2013). Therefore, we relied more heavily on these indices to determine the optimal number of classes in our final model.…”
Section: Discussionmentioning
confidence: 99%